Diagnostic difficulty arising from rectal recovery in ulcerative colitis. Issue 4 (April 1996) - Levine, T S; Tzardi, M; Mitchell, S; Sowter, C; Price, A B
Abstract : AIMS: To ascertain whether the dogma that a normal rectal biopsy precludes a diagnosis of ulcerative colitis is correct. METHODS: Rectal biopsy specimens from a prospective group of 24 asymptomatic patients, with an established diagnosis of ulcerative colitis, were examined in a blinded study alongside 10 normal rectal biopsy specimens from an age and sex matched patient cohort without ulcerative colitis. Each biopsy specimen was assessed by three pathologists and ascribed to one of four categories: normal; borderline abnormality (one or more minor nonspecific abnormalities which, when combined, did not fulfil the minimal acceptable criteria for a diagnosis of ulcerative colitis); minimal features of chronic ulcerative colitis; and unequivocal ulcerative colitis. RESULTS: Two patients with ulcerative colitis had normal biopsy specimens; nine specimens were categorised as borderline abnormality, one as showing the minimal changes of chronic ulcerative colitis, and 12 as having the typical changes of chronic ulcerative colitis. Thus, 11 (46%) of the 24 patients had a rectal biopsy specimen that was devoid of the acceptable attributes on which a diagnosis is established, despite a confident previous diagnosis. Ten of these 11 cases had disease limited to the rectum. Review of all previous histological biopsy specimens (n = 164) and clinical data, including drug treatment, failed to identify any attributes that might be prognostic markers for future rectal mucosal healing. CONCLUSIONS: A normal rectal biopsy specimen, though uncommon, may occur in longstanding colitis. Moreover, in 46% of these asymptomatic but established cases the degree of healing may preclude a diagnosis of ulcerative colitis without comprehensive clinical and radiological details. Pathologists need to be aware of this minimal end of the spectrum of disease.